Formulating a 100-year strategy for managing coastal hazard risk in a changing climate: Lessons learned from Hawke's Bay, New Zealand. Issue 127 (January 2022) - Ryan, E.J.; Owen, S.D.; Lawrence, J.; Glavovic, B.; Robichaux, L.; Dickson, M.; Kench, P.S.; Schneider, P.; Bell, R.; Blackett, P.
Abstract: Decision-makers, managers and communities in low-lying coastal regions face many challenges in planning for and adapting to escalating coastal hazard risk, given uncertainty about sea-level rise and complex and contested environmental and socio-economic futures. Collaborative and participatory approaches can help to address such challenges and enable proactive adaptation. However, there is limited empirical evidence of such approaches yielding outcomes that can genuinely be described as shifting business as usual, and fewer still that have informed institutional change. This paper provides such evidence based on an assessment of a novel collaboration between local government, Māori, stakeholders, community members, consultants and researchers in the formulation of a 100-year coastal hazard management strategy in Aotearoa New Zealand. Thematic analysis of interviews, surveys and workshop materials was used to distil lessons learned by participants involved in formulating this anticipatory long-term strategy. Results indicated the importance of deliberative, flexible and transparent governance processes that can enable collaboration amongst Māori, local and region-wide stakeholders, in a process consistent with and supported by the national governmental frameworks, and regulatory and non-regulatory measures. The importance of aligning scientific, local and Indigenous knowledges is highlighted. Furthermore, novel tools and methodologies were used in the strategy formulation process, hitherto not applied in a real-life coastal decision-making process, to address changing risk over time and uncertainties. This enabled the tailoring of strategic planning and decision processes to reflect local contexts and governance interactions. Adaptive pathways were developed to enable short-term actions to be taken while leaving open long-term options and alternative pathways available for future adjustment as the hazards and impacts intensify. The lessons learned from the development of the coastal management strategy offer insights to support future collaborative decision-making processes in climate change adaptation. They advance scholarly understanding about how sea-level rise risks can be addressed in a long-term strategic formulation process in a dynamic and 'fit-for-purpose' manner. Graphical Abstract: ga1 Highlights: We thematically analysed the formulation of a 100-year coastal hazards strategy. Key themes emerged to reveal lessons learned from the process. Collaborative and flexible governance processes contributed to building trust. Proactive, tailored decision tools enabled development of adaptation pathways. Scientific, technical, local and Indigenous knowledges were incorporated.